The experience of curricular modification of a curriculum during pandemic times (Revista Electrónica Calidad en la Educación Superior, 2023)
The Master of Education (ME) began in 1995, and since then, it has gone through different redesign processes, being the most recent a curricular modification. The pandemic and post-pandemic period evidenced the need to make adjustments to the curriculum based on the new demands of the target audience and the emerging context. This triggered the ME to opt for the virtual modality as a form of teaching delivery, reorienting curricular flexibility and the internationalization of the curriculum. This restructuring led to the modification of the subject of study and the final interest of knowledge, the strengthening of teaching skills, the pedagogical and methodological strategy, and the professional profile of the graduate person.
Keywords: Curricular modification; emerging technologies; virtual modality; pedagogical praxis; innovation